Evaluación del efecto de cuatro niveles de inclusión de palmiste en raciones para vacas en producción, en la finca Punzara de la UNL - Criollo Jiménez, Mirian Vanesa (2017)
The present research work was carried out in the Experimental Farm "Punzara" of the Universidad Nacional de Loja, it was a imed to evaluate the use of supplementary rations with different inclusion levels of palm kernel in crossbred Holstein cows kepton grazing. Four treatments were evaluated as follows: T1: ration without palm kernel, (control); T2: ration with 10% of palm kernel; T3: ration with 20% of palm kernel and T4: ration with 30% of palm kernel. Four crossbred Holstein cows of different ages were used, with a naver age weight of 505.5 kg and a naver age daily production of 9.7 liters; which were distributed, according to 4x4 Latin square design, with four treatments and four experimental periods. The variables studied were: bromatological composition of the palm kernel and experimental rations, consumption of food, milk production, milk quality, weight change and profitability. The results showed that the palm kernel presents a significant nutritional value with 12.31% of protein and 10.2% of fat; mean while the experimental rations presented small variations according to the levels of inclusion of palm kernel, thus the ration one (without palm kernel) presented a higher protein content with 22.86% and a lower fiber content with 9.66%; while ration four (30% of palm kernel) presented values of 16.65% and 18.48% for protein and fiber respectively. The use of supplementary rations with different levels of inclusion of palm kernel produced an in crease in milk production at 0.8l/cow/day; however, the total solids and fat content decreaseds lightly. It is concluded that the use of palm kernel in supplementary rations in production allows to increase milk production although its quality decreases slightly.